Trends in Antimicrobial Resistance Pattern of Klebsiella Bacteremia over a 6 Years Period (2010-2015) in a Hemodialysis Centre in Pakistan - Badlani, Sanjay; Dodani, Sunil Kumar; Nasim, Asma; Babar, Zaheeruddin; Azmi, Maliha (Infectious Diseases Journal of Pakistan, 2022)
Background: Klebsiella spp. is the commonest cause of bacteremia in dialysis patients from our center.A rising trend of antimicrobial resistance among Klebsiella has been reported from Pakistan. We studied the trends of antimicrobial resistance over 6 years in dialysis patients. Methods: Sindh Institute of Urology and Transplantation (SIUT) is a 750 bedded tertiary care hospital in Karachi, Pakistan. Around 500 patients are offered outpatient dialysis daily. We did a retrospective data analysis of all blood cultures sent from outpatient hemodialysis unit with isolation of Klebsiella spp. in the years 2010, 2012, 2014 and 2015. The resistance pattern of ceftriaxone, piperacillin-tazobactam, ciprofloxacin, trimethoprim-sulfamethoxazole, amikacin and imipenem were compared over a 6 years’ period. Results: A total of 27,852 blood cultures were received during the study years, out of which 19670 (70.6%) were positive for any microbial growth. Around 5325 (27%) were Klebsiella spp. There was an increase in percentage of Klebsiella spp bacteremia over the years, range from 19-35%. The antimicrobial sensitivity pattern changed over years. Resistance was lowest against imipenem in 2010 around 1%, which increased to 19% in 2015. Conclusion: There is a gradual rise in Klebsiella bacteremia in dialysis unit. Resistance to broad-spectrum antimicrobials has increased significantly with around twenty-fold increase in imipenem resistance over the last 6 years. We need a robust stewardship program for judicious use of antimicrobials and better infection control measures to contain increasing resistance.